Miliary Never-Smoking Lung Adenocarcinoma With Large Pleural Effusion Mimicking Tuberculosis - Fadi Aldaghlawi; Ziad Shaman; Johnathon DallaRosa; Shoji Shimizu; Linlin Yang; Michael Infeld (Annals of Internal Medicine: Clinical Cases)
Miliary nodules are an uncommon pattern of hematogenous metastasis to the lung. Here, we present a case of 54-year-old nonsmoking woman with history of previous tuberculosis exposure who was found to have a metastatic miliary lung adenocarcinoma and a unilateral large pleural effusion. This case provides an example of an uncommon constellation of radiographic findings that were shown to be due to metastatic lung adenocarcinoma.